الاَثار القانونية للعقود الإلكترونية عبر الإنترنت دراسة مقارنة - أرباب, يوسف زكريا عيسي (Gezira Journal of Economic and Social Sciences; مجلد 10 عدد 1 (2019), 2019)
يسعى الباحث من خلال هذا البحث بالتحقيق والتأصيل لبيان الاَثار القانونية للعقود الإلكترونية عبر الأنترنت، (إلتزامات البائع بتسليم المبيع وإلتزمات المشترى)، وذلك من خلال المدوّنات الفقهية والقانون الوضعى، حيث درس الباحث بالتحليل مفهوم العقد الإلكتروني، والعقد الإلكترونى هو ذلك العقد الذى يتكوّن وينفّذ عن طرق أو طريقة من طرق وسائل الاتصال عن بعد والتى هى ليست من العقود المسماة، كذلك تناول الباحث الاَثار المترتبة على العقود الإلكتروني عبر الانترنت فيما يتعلّق بإلتزامات البائع بتسليم المبيع والتزامات المشتري بدفع الثمن، وسلك الباحث المنهج الاستقرائى التحليلى حيث توصل الباحث الى جملة من النتائج والتوصيات أهمّها، أنّ العقد الإكتروني من طبيعة العقود الرضائية ولايختلف عن العقد التقليدي إلاّ في الوسيلة التى يتم بها، وهي وسائل إلكترونية. ويوصى الباحث بالاهتمام والتعرّف على كتب الفقه الاسلامى ومعرفة النوازل وايجاد النظائر لها فى كتب الفقه الاسلامى القديمة ثم استخراج الأحكام بناءاً على ذلك .             Through this research the researcher endeavor to investigate, re-originate and clarify the legal effects for the electronic contracts via internet, (seller’s obligations to handover the goods and the purchaser obligations) through the legal and juristic and blogs, where the researcher studied analytically the concept of the electronic contract: electronic contract is the contract that consists and executed by the means or methods of further mass media (it is not from the named contracts, also the researcher cast light on the effects of the electronic contract via the internet regarding the sellers obligations to handover and the purchaser paying obligations. The researcher followed the inductive analytical method. The study comes up with many results, such as: electronic contract is from the nature of the satisfaction contracts, it is not differ from the classical contract otherwise the electronic tools which used to perform the contract. Depending on the above result the researcher recommends those juristic books and knowing episodes, in order to find its isotopes in Islamic juristic ancient books, then extracting the rules upon that.